(untitled) (The Lumbini Journal of Business and Economics, 2023)
The purpose of this research paper is to reveal the relationships among green knowledge management, green innovation, and green innovation culture. These relationships were assessed using correlation analysis and hays process macro. Data were gathered from full-time cement factory employees having designations officers and above (N: 260) in the Lumbini Dhakdhai industry corridor region of Nepal. The results indicate that green knowledge management has a positive effect on green innovation and green innovation culture. Accordingly, green knowledge management is an important determinant of green innovation and green innovation culture. In addition, green innovation culture acted as a complementary partial mediator of the effects of green knowledge management on green innovation. Specifically, green knowledge management predicted green innovation, which in turn predicted green innovation culture. Finally, considering that causal studies on green knowledge management, green innovation and green innovation culture in the cement industry are limited, this study may contribute to understanding how green knowledge management affects green innovation in the cement industry.